Menilik diplomasi pendidikan Agama Buddha oleh Kerajaan Sriwijaya dalam Prasasti Nalanda abad ke-9 M - Guntur Adi Putra; Yuliati Yuliati (Historiography: Journal of Indonesian History and Education, 2021)
This paper is a study that reveals the existence and diplomatic relations between Buddhist religious education established by the Sriwijaya Kingdom and the Pala Kingdom based on the Nalanda Inscription in the 9th century AD. Srivijaya's fame lies not only in its strength as a maritime empire but also in the aspect of religious diplomacy. The Buddhist teachings adopted by the Srivijaya Kingdom were very strong and attracted monks to study in this kingdom. One of the monks who had studied in Sriwijaya was I-Tsing from China. Through this, we can know that Srivijaya was once the center of Buddhism in Southeast Asia. The Srivijaya Kingdom then established diplomatic relations with Nalanda in India to strengthen the skills of its students to learn more about Buddhism. In Nalanda, Maha Vihara Nalanda is also touted as a center for learning Buddhism in Asia. Thus, based on the Nalanda Inscription which was made in the 9th century, it is known that Srivijaya-Nalanda agreed to establish educational cooperation to increase the capacity and spread of Buddhism in Asia. This study uses a literature study with a qualitative approach. In addition, to analyze the content of existing sources, the researcher also uses historical methods consisting of heuristic steps, source criticism, interpretation, and historiography. Tulisan ini merupakan kajian yang mengungkap keberadaan dan hubungan diplomatik antara pendidikan agama Buddha yang dijalin oleh Kerajaan Sriwijaya dan Kerajaan Pala berdasarkan Prasasti Nalanda pada abad ke-9 Masehi. Ketenaran Sriwijaya tidak hanya terletak pada kekuatannya sebagai kerajaan maritim tetapi juga dalam aspek diplomasi agama. Ajaran Buddha yang dianut oleh Kerajaan Sriwijaya sangat kuat dan menarik para biksu untuk belajar di kerajaan ini. Salah satu biksu yang pernah belajar di Sriwijaya adalah I-Tsing dari Tiongkok. Melalui ini, kita dapat mengetahui bahwa Sriwijaya pernah menjadi pusat agama Buddha di Asia Tenggara. Kerajaan Sriwijaya kemudian menjalin hubungan diplomatik dengan Nalanda di India untuk memperkuat keterampilan para siswanya untuk belajar lebih banyak tentang agama Buddha. Di Nalanda, Maha Vihara Nalanda juga digadang-gadang sebagai pusat pembelajaran agama Buddha di Asia. Dengan demikian, berdasarkan Prasasti Nalanda yang dibuat pada abad ke-9 diketahui bahwa Sriwijaya-Nalanda sepakat untuk menjalin kerjasama pendidikan untuk meningkatkan kapasitas dan penyebaran agama Buddha di Asia. Penelitian ini menggunakan studi kepustakaan dengan pendekatan kualitatif. Selain itu, untuk menganalisa isi dari sumber yang ada, peneliti juga menggunakan metode sejarah yang terdiri dari langkah heuristik, kritik sumber, interpretasi, dan historiografi.